Carbon quantum dots implanted sulfonated 2D-MoS2 for hydrogen evolution - Sarkar A.; Ganesh G.; Qamar U.; Singh V.K.; Sharma R.; Srivastava A.; Venugopal G.; Jose R.; Das S. (My University, 2025)
We report the enhancement of electrocatalytic activity in sulfonate (−SO3H) group functionalized two-dimensional molybdenum disulfide (2D-s-MoS2) nanosheets for their use in hydrogen evolution reaction (HER). These as-developed nanosheets have been decorated with sustainable biomass-derived carbon quantum dots (CQDs) via a sonochemical method, creating a s-MoS2-CQD composite material. This innovative composite demonstrates significantly improved electrocatalytic performance for the hydrogen evolution reaction (HER) via water splitting. In particular, incorporating CQDs on 2D-s-MoS2 overcomes many limitations, as observed in pristine 2D-MoS2 and 2D-s-MoS2, especially regarding low electrical conductivity and restricted electrocatalytic activity on the basal plane. Incorporating CQDs enhances electron transfer efficiency, increases the availability of active sites, and enhances overall conductivity. As a result, the s-MoS2-CQD achieves remarkable HER performance, featuring a lower overpotential of ∼ 273 mV and a reduced Tafel slope of 67 mV/dec compared to s-MoS2. These enhancements signify faster reaction kinetics, accelerated H* adsorption–desorption, and greater catalytic efficiency. Furthermore, using sustainably synthesized CQDs positions this approach as a cost-effective, scalable, and environmentally friendly alternative to traditional noble-metal catalysts. This research highlights the potential of functionalized two-dimensional materials, such as s-MoS2, implanted with zero-dimensional materials, such as CQDs, to advance sustainable hydrogen production technologies, thereby contributing to the global shift towards clean energy solutions. © 2025 Elsevier B.V.